An Accelerated Learning Model of the Kitab Kuning in Madurese Pesantren: A Multi-Site Study - Lailaturrohmah Lailaturrohmah; R. Kholisol Muhlis; A. Hufron; Abd Warits; Suyany Marth (Graduate School of UIN Syarif Hidayatullah Jakarta, 2025)
The practice of Kitab Kuning learning in Indonesian pesantren represents a fundamental aspect of Islamic scholarly transmission. However, long-standing teaching methods like sorogan and bandongan are coming under more pressure from modern educational needs, especially when it comes to getting students to pay attention and use their time wisely. While numerous acceleration initiatives have been implemented in various pesantren, systematic and empirically validated models of accelerated Kitab Kuning learning are still inadequately examined. This research examines pedagogical methods in three pesantren located in Madura and develops an evidence-based accelerated learning model for classical Islamic texts. Utilizing a qualitative descriptive-exploratory design, data were gathered via in-depth interviews, participant observation, and document analysis at Almadinah Ganding Sumenep, LPI Maktuba al-Majidiyah Plakpak Pamekasan, and Darussalam Puncak Palengaan Pamekasan. The results show that traditional learning methods usually take students three to four years to master basic text, but accelerated teaching methods cut this time down significantly by using experiential, active, and contextual learning methods. The study advances theoretical understanding by framing accelerated textual literacy within pesantren pedagogy, enhances methodological approaches by suggesting a versatile multi-strategy instructional design applicable in various pesantren settings, and offers empirical validation through field-based evidence of its efficacy. The uniqueness of this research resides in the formulation of a structured acceleration model that maintains the epistemic authority and scholarly ethos of pesantren while addressing modern pedagogical challenges. These results have useful implications for developing curricula and training teachers in Islamic schools.